IPTEK BAGI MASYARAKAT MESIN PENCACAH PAKAN TERNAK SAPI BERUPA CACAHAN HIJAU - Suzen, Zaldy Sirwansyah; Hasdiansah, Hasdiansah; Zulfitriyanto, Zulfitriyanto; Pristiansyah, Pristiansyah; Erwansyah, Erwansyah; Sugianto, Sugianto; Ahadiatullah, Wassi; Oktavianto, Mario (Pusat Penelitian dan Pengabdian Kepada Masyarakat, 2025)
Animal feed is an important factor that must be considered to increase the productivity of providing green fodder both in quality and quantity, where in the provision of cattle feed is still done manually using hands with the help of machetes and sickles to chop the feed, especially for cattle breeders of the Puding Jaya II Farmer Group in Puding Village, Merawang District, Bangka Regency. The purpose of this study is to assist in the processing of livestock feed conventionally or manually by designing a chopping machine so that it can make its own cemboran and chopped feed using available materials such as special grass leaves for cattle feed or oil palm leaves so that they are easy for cattle to chew. The method used starts from designing a chopping machine that can be used as a chopping tool for raw materials for livestock feed in the form of odot plants, Indigofera, Chinese petai, jackfruit leaves, elephant grass, palm fronds and leaves which are favorite green fodder for cattle so that it is expected to lighten the burden and make it easier for cattle breeders to get livestock feed that is ready to be eaten by cattle. in an effort to increase livestock feed production can increase as expected to reach 200-300 percent.